Preparation and studying of some properties of polymer composites reinforced with natural and artificial fibers - Hameed, Awham M. (Iraqi Journal of Physics, 2019)
This work concerns the thermal and sound insulation as well as the mechanical properties of polymer matrix composite reinforced with glass fibers. These fibers may have dangerous effect during handling, for example the glass fibers might cause some damage to the eyes, lungs and even skin. For this reason the present work, investigates the behavior of polymer composite reinforced with natural fibers (Plant fibers) as replacement to glass fibers. Unsaturated Polyester resin was used as matrix material reinforced with two types of fibers, one of them is artificial (Glass fibers) and the other type is natural (Jute, Fronds Palm and Reed Fibers) by hand lay-up technique. All fibers are untreated with any chemical solvent. The Percentage of mixing was (90 wt. %) of the matrix while the weight fraction of each type of fibers was fixed (10 wt. %). The mechanical tests included impact and flexural strength tests. The results showed that the impact strength and flexural strength of the composites reinforced with Jute fibers is higher than that of Glass fibers and other natural fibers. The coefficients of thermal conductivity of the composites were measured by Lee’s disc apparatus, the results show that the thermal insulation of the composite reinforced with jute fibers is higher than that of glass fibers and other natural fibers. The acoustic insulation of the composites reinforced with Jute fibers showed excellent result in insulation compared with glass fibers and other natural fibers.